Analysis of Destructive Processes in Unloaded Early-age Concrete with the Acoustic Emission Method. (2015) - Bacharz, Magdalena; Goszczyńska, Barbara; Trąmpczyński, Wiesław
Abstract: The study presents the analysis of destructive processes that occur in early-age concrete with the use of the IADP method of acoustic emission signal analysis. The tests were conducted for concrete specimens made with basalt aggregate, which was cured at a constant temperature of 22° C, but were different with respect to cement class, admixtures used and the curing methods. Three classes of AE signals were identified. The signals were generated by destructive processes related mainly to concrete shrinkage due to water evaporation and described as: microcracks at the aggregate – cement paste interface, microcracks in the cement paste, and the formation of microcracks on concrete surface. It was shown that the IADP method could be used to identify and evaluate the destructive processes that develop in early-age concrete.